Fluvial biofilms exposed to desiccation and pharmaceutical pollution: New insights using metabolomics - Serra-Compte, Albert; Corcoll, Natàlia; Huerta, Belinda; Rodríguez-Mozaz, Sara; Sabater, Sergi; Barceló, Damià; Álvarez-Muñoz, Diana (Science of The Total Environment, 2018)
In many arid and semi-arid systems, biological communities in river ecosystems are submitted to flow interruption and desiccation, as well as to the impact of urban wastewaters. In this work, we studied (using a LC-LTQ-Orbitrap) the metabolomic response of biofilm communities exposed to both hydrological and chemical stressors. Fluvial biofilms were exposed to a mixture of 9 pharmaceuticals at a total concentration of 5000ng/L (mimicking concentrations and compounds found in polluted aquatic environments) and/or to seven days of desiccation, under laboratory conditions. The biosynthesis of fatty acids was the main metabolic pathway disrupted in biofilms. Endogenous biofilm's metabolites (metabolome) altered due to these stressors were identified. The metabolites that significantly changed only due to one of the stressors could be proposed as potential specific biomarkers. A biomarker of pharmaceutical exposure was the lysophosphatidic acid, which decreased a 160%, while for desiccation stearidonic acid (increased 160%), 16-Oxohexadecanoic acid (increased 340%) and palmitoleic acid (decreased 290%) were the biomarkers proposed. Besides, other metabolites showed different responses depending on the treatment, such as palmitic acid, linolenic acid, behenic acid, lignoceric acid and azelaic acid. The Carbon:Phosphorus (C:P) molar ratio increased due to all stress factors, whereas the algal community composition changed mainly due to desiccation. A possible relationship between those changes observed in structural parameters and the metabolome of biofilms was explored. Overall, our findings support the use of metabolomics to unravel at molecular level the effects from chemical and physical stressors on complex microbial communities, such as biofilms, and pinpoint biomarkers of exposure.
Keywords: Biofilms; Biomarkers; Environmental stressors; Metabolomic profiling; dept.che